Source-to-sink controls on reservoir distribution in the southeastern Huizhou Depression, Pearl River Mouth Basin, South China Sea - Peng, Guangrong; Liu, Pei; Luo, Ming; Song, Penglin; Liu, Hanqing; Li, Xiaoyan; Wang, Wenyong; Yu, Sa; Han, Bo (Frontiers in Earth Science, 2026)
This study combines petrological, logging, and seismic analyses to investigate the development of favorable reservoirs within a source-to-sink framework. Here, we focus on the Upper Enping Formation of the Huizhou 26 Sag, located in the Huizhou Depression of the Pearl River Mouth Basin. In general, the study area can be divided into three segments, each controlled by different boundary faults. The source-to-sink analysis first reveals that five major source catchments, each with distinct drainage area and relief, developed within Mesozoic intrusive rocks, enabling a quantitative assessment of the sediment supply capacity for each catchment. Sediment transport systems are then evaluated based on the characteristics of boundary faults. Specifically, fault throw influences the preferred drainage pathways into the lake, while fault geometry and configuration regulate drainage convergence upon entry. When both source catchments and transport systems are optimal, braided river deltas form within the lake, as observed in the central and northern segments; otherwise, fan deltas prevail, as in the southern segment. In this source-to-sink context, the factors influencing high-quality reservoirs are further investigated. First, sedimentary facies exhibit first-order control on reservoir quality, with braided river delta plain facies having much better reservoir properties than fan delta facies. Secondly, enhanced transport in areas such as multi-stepped faults and paleo-uplifts can significantly improve reservoir quality. Finally, volcanic material infill can further modify reservoirs through various diagenetic processes. Taken together, this study demonstrates that braided river deltas within source-to-sink systems characterized by optimal catchment and transport conditions should serve as the primary targets for favorable reservoirs. In contrast, in areas dominated by fan deltas, only sandstones significantly influenced by processes such as enhanced transport and dissolution can develop into high-quality reservoirs. These insights contribute to advancing the exploration of the Enping Formation and guiding future exploration of the deeper strata in the southwestern Huizhou Depression.